B and T cell epitope-based peptides predicted from clumping factor protein of Staphylococcus aureus as vaccine targets. (November 2021) - Dey, Jyotirmayee; Mahapatra, Soumya Ranjan; Singh, Pratima; Patro, Swadheena; Kushwaha, Gajraj Singh; Misra, Namrata; Suar, Mrutyunjay
Abstract: Staphylococcus aureus infection is emerging as a global threat because of the highly debilitating nature of the associated disease's unprecedented magnitude of its spread and growing global resistance to antimicrobial medicines. Recently WHO has categorized these bacteria under the high global priority pathogen list and is one of the six nosocomial pathogens termed as ESKAPE pathogens which have emerged as a serious threat to public health worldwide. The development of a specific vaccine can stimulate an optimal antibody response, thus providing immunity against it. Therefore, in the present study efforts have been made to identify potential vaccine candidates from the Clumping factor surface proteins (ClfA and ClfB) of S. aureus . Employing the immunoinformatics approach, fourteen antigenic peptides including T-cell, B-cell epitopes were identified which were non-toxic, non-allergenic, high antigenicity, strong binding efficiency with commonly occurring MHC alleles. Consequently, a multi-epitope vaccine chimera was designed by connecting these epitopes with suitable linkers an adjuvant to enhance immunogenicity. Further, homology modeling and molecular docking were performed to construct the three-dimensional structure of the vaccine and study the interaction between the modeled structure and immune receptor (TLR-2) present on lymphocyte cells. Consequently, molecular dynamics simulation for 100 ns period confirmed the stability of the interaction and reliability of the structure for further analysis. Finally, codon optimization and in silico cloning were employed to ensure the successful expression of the vaccine candidate. As the targeted protein is highly antigenic and conserved, hence the designed novel vaccine construct holds potential against emerging multi-drug-resistant organisms. Graphical abstract: Image 1 Highlights: Clumping factor protein plays a major determinant in the virulence of S. aureus. Immunoinformatic approaches was employed to design multi-peptide vaccine to induce humoral and cellular immune responses. Immunological potential including the allergenicity, antigenicity, and population coverage analysis were evaluated. Molecular docking and MD simulation exhibited a strong and stable binding affinity between vaccine-TLR2.